Shalom Educational Model and the Paradigm Shift in the Social Work Training in the Democratic Republic of Congo (DRC) - Moleka, Pitshou, Basikabio (My University, 2021)
Social work is a discipline that was introduced into an academic curriculum in the DRC not long ago. It is with the repetition of the phenomena of urban banditry and that of street children that the various stakeholders have thought of training professionals in this field. But is said training effective and appropriate? In this article, I examine through a sample the academic curriculum in the DRC and propose avenues’ starting from the biblical model of shalom, which is a four-dimensional model, responding to contextual and spiritual needs. The article contains seven parts: the first point will be the introduction, in the second point there will be a brief contextual presentation of DR Congo, the third point is about the method used in this article, the fourth point will be the sample of social work curricula, the fifth point will be analysis and assessment of this curricula, in the sixth point I will show the implications of shalom model in the social work training and the last point will be the conclusion.
Keywords: Shalom; education model; social work; faith; spirituality; decolonization; Democratic Republic of Congo